Detection of L-Tyrosine by electrochemical method based on binary mixed CdO/SnO2 nanoparticles. (15th October 2020) - Alam, M.M.; Uddin, M.T.; Asiri, Abdullah M.; Rahman, Mohammed M.; Islam, M.A.
Graphical abstract: Highlights: CdO/SnO2 nanoparticles prepared by facile wet-chemical method. Highly sensitive in-situ L-tyrosine sensor by reliable electrochemical method. L-tyrosine-sensor exhibits the lower detection limit within short response time. Practically validated the real biological serum samples. Effective L-tyrosine -sensor for health care and biomedical fields. Abstract: Here, the nanoparticles (NPs) of CdO/SnO2 were prepared by co-precipitation method in alkaline phase at low temperature. The characterization of CdO/SnO2 NPs were analyzed by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscope (FESEM), X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDS) analysis. To fabricate the sensor, glassy carbon electrode (GCE) was coated by CdO/SnO2 NPs with 5% nafion suspension. The resulted sensor was applied to detect L-Tyrosine (L-Tyr) in buffer phase. A linear relation current versus concentration known as calibration curve was made. The sensor sensitivity (11.848 µA µM −1 cm −2 ) is calculated from the slope of calibration curve. Recognizing the maximum linear region in calibration curve (regression coefficient R 2 = 0.99), the linear dynamic range (0.1 nM–0.01 mM) is used. Finally, the lower limit of detection (97.93 ± 4.89 pM) is estimated by applying the signal to noise ratio of 3 from the calibration curve. During the sensing performances, it was found as reliable, reproducible and long-term stable sensor and validated to detect the real biological samples by electrochemical approach in room conditions.